Developments in Psychiatry in India: Clinical, Research and Policy Perspectives - Malhotra, Savita (Springer, 2015)
The volume evaluates major developments in psychiatry in India from the 1950s, and highlights the areas where Indian psychiatry has contributed to the development of the subject worldwide. The chapters review international as well as Indian developments in psychiatry and its sub-specialities. A wide range of clinical, research and policy-related topics have been covered in the volume, which begins with an overview of the history of psychiatry in India, moving on to developments in various sub-specialities of psychiatry in the last 60 years or so. It then specifically discusses developments in psychology and psychodynamics, general adult and child psychiatry, substance use psychiatry, community psychiatry, liaison psychiatry, and other psychiatric sub-specialities. Developments in treatment, the status of training and service in psychiatry and legal issues related to the practice of psychiatry in India are also included. The contributors to this volume are nationally and internationally recognized experts in different areas of psychiatry. Most of them have had some association, or are currently associated, with the Department of Psychiatry at the Post Graduate Institute of Medical Education and Research, Chandigarh, India.